Cemitérios e vulnerabilidade ambiental: um diagnóstico do risco de contaminação no perímetro rural de Francisco Beltrão - PR - Cristofoli, Karise (2014)
The discussion of the problems linked to risk of contamination brought about the cemeteries has been restricted to a relatively small portion of society. It is however, an issue of significant importance in the sphere sanitarian, as in the environmental sphere. This study highlights the main problems that cemeteries can cause when it ignored the set of statutory federal and state levels, among which stands out the CONAMA resolution No. 335/2003, the Code of Health of Paraná Law No. 13331/SEMA 2001 and Resolution No. 002/2009. In this context, the present study had the objective was accomplished: the location and mapping of rural cemeteries Francisco Beltrão - PR; the main types of research conducted in these burial cemeteries; risk assessment of environmental contamination in the areas of direct and indirect influence of these developments; conduct the survey and systematization of corrective and preventive measures for areas where irregularities are diagnosed in cemeteries. Several methodological procedures, among which stand out were used to conduct this work: the identification and mapping of existing cemeteries in the rural area of the city of Francisco Beltrão - PR; the application of questionnaires to representatives of communities that have cemetery and interviews with representatives of government agencies responsible for licensing and environmental sanitation sector in the city. In Fieldwork was possible to collect water from fifteen points and mount a database on aspects of the use and distribution of natural elements within and in the neighborhood of cemeteries. As a result we identified 51 municipal cemeteries located in a rural area, of which 95% are held and managed by the community itself without assistance from the government. All cemeteries higher risk of environmental contamination, however, the degree of environmental impact varies with the concurrence of non-conformities in the practice of burials and maintenance of these cemeteries. Through the study concluded that there is no technical support by the Municipality and the emerging need of conducting clarification and training process in communities, especially those residents who become responsible for the daily practices implemented under the cemeteries. We underline the statement at work inserting environmental education activities in order to prevent and, if possible, to minimize the negative impacts of cemeteries.